Analisis Pengendalian Kualitas Produksi Carica Menggunakan Metode Seven Tools Studi Kasus Pada CV Gemilang Kencana - Zidan Muhammad Firmansyah; Suseno Suseno (Jurnal Penelitian Rumpun Ilmu Teknik, 2023)
CV Gemilang Kencana is a company engaged in the manufacturing and processing industry of carica sweets which was established on October 10, 2013. The carica fruit itself is a fruit that grows in the highlands of Wonosobo. From the production of carica sweets, there are several problems during the production process, including defects in packaging products such as slanted labels, inappropriate product weight, damaged/leaky packaging cups, with a total product defect of 474 cups with the most defects on February 29, 2023. from product defects that have been described, therefore quality control is needed to reduce product defects, namely by using the seven tools method in quality control. The control chart table shows the most defects, namely on the 29th with a total of 43 cups of defects while the highest level of disability is on the 7th with a middle limit value of 0.0079, an upper limit of 0.012692, and a lower limit of 0.003108. The histogram graph shows the highest defect, namely the damaged / leaky packaging cup, after that the product weight defect does not match and the lowest is the slanted label. In the pareto diagram through processing, a pareto diagram is made with the most dominant result of defects, namely damaged/leaking cup packaging with a value of 47.68%. Based on the scatter diagram, which involves two variables, namely the variable number of production and total product defects. Based on the scatter diagram, it can be seen that the shape of the distribution has a positive correlation or relationship between the amount of production and product defects. Based on fishbone analysis, the causes of product defects are from several factors, namely machine, human, environmental, and methods factors so that companies take preventive or corrective actions to minimize defects during the production process.